PENGEMBANGAN LEMBAR KERJA PESETA DIDIK BERBASIS STEM (SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS) PADA MATERI TERMOKIMIA - Novia Nur Sakinah; Junifa Layla Sihombing; Susilawati Amdayani (Universitas Negeri Medan, 2022)
Abstract :Development of STEM-Based Student Worksheets (Science, Technology, Engineering And Mathematics) on Thermochemical Materials. This study aims to determine the level of feasibility, practicality, and student responses to STEM-based student worksheets on thermochemical material. The subjects of this study were 2 material expert validators and 2 media expert validators, 2 chemistry teachers and all students of class XI MIA 1. The research design used a 4-D model (Define, Design, Develop, and Disseminate). The instruments used are interview guidelines, validation sheets by validators, practicality questionnaires by teachers, and student response questionnaires. The data analysis technique used presentation method. The results obtained that the average percentage of assessment by material experts is 83.03% in the appropriate category, by media experts at 98.2% in the very appropriate category, the practicality level by the teacher is 98.5% in the very practical category, and the results of student responses is 94.44% answered